Architecting the Net-Zero Frontier: Systemic Implementation Strategies for Sustainable Infrastructure in the AWS Ecosystem - RaviKumar Bhuvanagiri (International Journal Software Engineering and Computer Science (IJSECS), 2026)
Global digital infrastructure in 2026 operates under mounting pressure from climate regulation, tightening energy policy, and growing demands for corporate environmental accountability. Cloud migration is frequently positioned as a straightforward path to sustainability — yet that assumption holds only when customers take deliberate responsibility for what runs inside the cloud. The AWS Shared Responsibility Model makes this obligation explicit: AWS governs the physical layer, while customers own the workload architecture and its carbon consequences. This paper examines how sustainability principles — environmental stewardship, social equity, and economic resilience — can be systematically embedded into AWS IT project delivery. Drawing on empirical data from 2025–2026, we propose a three-layered decision-making model anchored in Silicon-Level Optimization, Geographic Carbon Intensity (GCI), and Temporal Workload Shifting. Each layer addresses a distinct decision horizon, from hardware selection at the design phase through operational lifecycle governance. Projects that adopted this model recorded a 30% reduction in carbon emissions and a 22% decrease in total cost of ownership (TCO), demonstrating that environmental responsibility and financial performance are not competing objectives.